Local Economic Development and Social Entrepreneurship After the Covid-19 Pandemic (Case: UMKM Cihil Food, Cihideung Ilir Village, Dramaga, Bogor Regency) - Siti Arneidha Naimah Marasabessy; Afiya Hashina Muhamnu; Tri Budiarto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The activities of the UMKM sector during the Covid-19 pandemic were hampered and triggered the emergence of various problems that led to business bankruptcy. This study aims to analyze the dynamics of the local economy and the stages of social entrepreneurship pursued by Cihil Food UMKM in developing their post-pandemic business in terms of an analysis of the potential and problems that these UMKM have. The research was conducted in Cihideung Ilir Village, Ciampea District, Bogor Regency which took place from February 2023 to May 2023. The data collection method used a qualitative approach through the stages of observation, documentation and in-depth interviews with informants who were processed through qualitative analysis. The results showed that the development efforts carried out by researchers on Cihil Food UMKM opened opportunities for UMKM to adapt to post Covid-19 conditions through the creativity and skills of each member.